Mass Spectrometry of Substituted 1H,6H-Pyrano[2,3-c]pyrazol-6-ones - Asif, Nadia; Chaudhry, Faryal; Naeem Khan, Muhammad; Guerra Cosenza, Alina; Penant Ellis, Gwynn; Ain Khan, Misbahul; Ali Munawar, Munawar; Iqbal, Sana; Aslam, Noreen (Asian Journal of Chemistry, 2013)
The mass spectra of some C- and N-alkyl and aryl substituted 1H,6H-pyrano[2,3-c]pyrazol-6-ones are presented. The fragmentation is initiated by the elimination of CO followed by a loss of hydrogen, rearrangement and then loss of a RCN group. Parallely a disproportionation gives RN2 which loses N2 to give the aromatic ion (m/z 77 or 91).